Fostering Openness to Rehabilitation and Reintegration of Criminals into Society in a Fearful World: The Moderating Role of Regulatory Focus. Issue 1 (2nd January 2020) - Buen, Adeluiesa; Lee, Eunro; Moss, Simon A.
ABSTRACT: Many scholars advocate the benefits of rehabilitation and reintegration of offenders to curtail crime and recidivism. Yet, discussions about criminal justice tend to reinforce the belief that crime is rife, amplifying fears around crime and promoting right-wing authoritarianism – the belief that people who do not obey authorities should be punished severely. Consequently, many citizens would like to maintain traditional punishment rather than shift the discourse to rehabilitation and reintegration. Governments may thus be reluctant to prioritize rehabilitation and reintegration. This study explored the possibility that interventions that inspire people to prioritize future aspirations over immediate duties, called a promotion regulatory focus, might diminish the extent to which fear of crime is related to both right-wing authoritarianism and attitudes toward rehabilitation, reintegration, and punishment. In this study, 207 participants completed an online questionnaire. As structural equation models revealed, right-wing authoritarianism mediated the positive association between fear of crime and punitive attitudes. Yet, if individuals prioritized immediate duties over future aspirations, fear of crime was not as likely to culminate in unfavorable attitudes to rehabilitation and reintegration. Accordingly, reward structures that honor progress to a greater extent than perhaps they punish shortfalls might foster more favorable attitudes to rehabilitation and reintegration.